Justification of indicators for determining military losses caused by combat actions - Kosaretskyi, Yevhenii (Social Development and Security, 2024)
Purpose: justification of the need to introduce additional indicators for determining military losses caused by combative actions. Method: analytical method, observation and formalization. Findings: A study was carried out and a formalization of costs related to the rehabilitation of military personnel and the training of military specialists for the defense forces was proposed. Quantitative indicators of environmental damage at the facilities of the Ministry of Defense of Ukraine were provided. Theoretical implications: The considered indicators for determining military costs and losses make it possible to increase the effectiveness of regulatory and legal support for assessing damage and injury caused by armed aggression. Value: The introduction of additional indicators for determining military losses makes it possible to obtain more complete and reliable information on the structure of the injury caused when forming the register of military damages. Future research: Further research should be aimed at revising military costs (losses) indicators and improving damage assessment mechanisms in the Ministry of Defense system.